Development RPP Based on Flipped Learning Model Material of Human Respiratory System - Dina Ratna Kumala; Ospa Pea Yuanita Meishanti (APPLICATION: Applied science in Learning Research, 2022)
The existence of the Covid-19 pandemic condition makes learning in each region different, including limited online and face-to-face learning as well as circulars from the government regarding the simplification of lesson plans into 1 sheet with 3 main components, making it a challenge for a teacher to reconstruct lesson plans globally. by adapting to the current situation. The purpose of this study was to develop Reconstruction RPP based on the Flipped Learning Model of Human Respiratory System Material to determine the feasibility of learning design based on a validation questionnaire of learning design experts and the attractiveness of RPP based on student responses. This study uses the ADDIE development model which has five stages, namely: 1) Analyze 2) Design 3) Develop 4) Implement, and 5) Evaluation. The subjects of this study were 2 experts on learning design validation and 10 students of class XI IPA 1 MAN 10 Jombang. The instrument used is a validation questionnaire of learning design experts and student response questionnaires. Data analysis techniques are quantitative and qualitative. The results showed that the validation of learning design experts obtained an average score of 93.75% with appropriate criteria and the results of the student questionnaire obtained a score of 84% with very interesting criteria. Based on these results, this RPP reconstruction can be applied to the respiratory system material in class XI humans at MAN 10 Jombang and it is hoped that in the future this Inspirational RPP reconstruction can be applied to other materials.